World class readings 3 : - Rogers, Bruce (McGraw- Hill, 2004)
World Class Readings is a theme-based series using engaging and up-to-date reading passages to help learners develop reading skills. For high intermediate learners, World Class Readings has broad range of activities involving skill building, reading comprehension, and vocabulary development